Author Correction: Regio- and stereoselective synthesis of tetra- and triarylethenes by N-methylimidodiacetyl boron-directed palladium-catalysed three-component coupling - E. Emily Lin (Nature Portfolio, 2019)
The previously published version of this Article contained errors in Fig. 1, where the B(MIDA) fragment was incorrectly labelled. These errors have been corrected in both the PDF and HTML versions of the Article.